Governance of natural resources: Highlights, lessons learned, and priorities for One CGIAR - CGIAR Research Program on Policies, Institutions, and Markets (International Food Policy Research Institute, 2021)
What are the drivers and consequences of tenure insecurity? PIM research under Flagship 5 addressed drivers and consequences of tenure insecurity from three angles: women’s rights, individual or household rights, and collective rights (where ownership or long-term use and/or management rights have been recognized or devolved to communities to some extent). Individual and household rights focus on agricultural land; collective rights on forests, rangelands, and water; and women’s rights consider the full range of resources.